Ascophyllum nodosum-Based Biostimulants: Sustainable Applications in Agriculture for the Stimulation of Plant Growth, Stress Tolerance, and Disease Management - Shukla, Pushp Sheel; Mantin, Emily Grace; Adil, Mohd; Bajpai, Sruti; Critchley, Alan T.; Prithiviraj, Balakrishnan (Frontiers in Plant Science, 2019)
Abiotic and biotic stresses limit the growth and productivity of plants. In the current global scenario, in order to meet the requirements of the ever-increasing world population, chemical pesticides and synthetic fertilizers are used to boost agricultural production. These harmful chemicals pose a serious threat to the health of humans, animals, plants and the entire biosphere. To minimize the agricultural chemical footprint, extracts of Ascophyllum nodosum (ANE) have been explored for their ability to improve plant growth and agricultural productivity. The scientific literature reviewed in this article attempts to explain how certain bioactive compounds present in extracts aid to improve plant tolerances to abiotic and/or biotic stresses, plant growth promotion and their effects on root/microbe interactions. These reports have highlighted the use of various seaweed extracts in improving nutrient-use-efficiency in treated plants. These studies include investigations of physiological, biochemical and molecular mechanisms as evidenced using model plants. However, the various modes of action of A. nodosum extracts have not been previously reviewed. The information presented in this review depicts the multiple, beneficial effects of Ascophyllum nodosum-based biostimulant extracts on plant growth and their defense responses and suggests new opportunities for further applications for marked benefits in production and quality in the agriculture and horticultural sectors.